Convergence Properties of the Gravitational Algorithm in Asynchronous Robot Systems - Cohen, Reuven; Peleg, David (SIAM journal on computing, 2005)
This paper considers the convergence problem in autonomous mobile robot systems. A natural algorithm for the problem requires the robots to move towards their center of gravity. This paper proves the correctness of the gravitational algorithm in the fully asynchronous model. It also analyzes its convergence rate and establishes its convergence in the presence of crash faults.